The effectiveness of liposomal doxorubicin hydrochloride in combination with cyclophosphan in the treatment of breast cancer in an experiment - L. A. Balykova; V. I. Inchina; T. V. Tarasova; L. M. Mosina; E. N. Gvozdikova; D. A. Khaydar; G. I. Myandina; S. M. Ryzhakin; I. V. Saushev (Исследования и практика в медицине)
Purpose of the study. To evaluate the antitumor efficacy of liposomal doxorubicin hydrochloride in combination with tamoxifen in the treatment of breast cancer.Materials and methods. The study included mongrel white rats (n = 30). A model of carcinogenesis (Walker 256 tumors) was created for all animals. Then we divided these rats into 3 equal groups: 1 control group (n = 10) - animals were monitored without treatment; 2 group (n = 10) - animals received neoadjuvant therapy: liposomal doxorubicin hydrochloride + cyclophosphan; 3 group (n = 10) - animals received neoadjuvant therapy with doxorubicin hydrochloride (non-liposomal) and cyclophosphan. Animals of the second and third groups received two cycles of neoadjuvant therapy. All animals were monitored for 1.5 months. We evaluated the effectiveness of antitumor therapy by measuring the size of tumors, the dynamics of their regression, and counting the number of metastases in the lungs. The toxic effects of doxorubicin hydrochloride were assessed by blood parameters: platelet and lymphocyte levels.Results. We recorded a significant inhibition of the growth of tumor nodes in the second group of rats on the 25th day from the start of the experiment compared with the first and third groups: 36004.7, 86112.1 and 38962.4 mm3, respectively. By the end of the 3rd week of the experiment, we also noted the formation of a tumor regression trend in the 2nd and 3rd groups of animals, which was reliably maintained until the end of the observation. At the end of the experiment, the number of metastases in the first group of animals was 3 times more, in the third group almost 1.5 times more than in the second (p < 0.05)Conclusion. The treatment of Walker 256 tumor with liposomal doxorubicin showed better efficacy and safety in comparison with non-liposomal doxorubicin. The tumor volume becomes smaller against the background of neoadjuvant chemotherapy with liposomal doxorubicin hydrochloride compared with its non-liposomal form, while there is no pronounced decrease in platelets and lymphocytes. We also recorded a significantly lower number of lung metastases in animals of the second group compared to other groups.